구강점막에 발생한 호지킨림프종의 증례보고 및 문헌고찰 - 이은수; HE YUZHU; 조혜중; SUN QIAOCHU; SHI SHUHAN; 김영; 김옥준 (대한구강악안면병리학회지, 42(6), 2018)
Extranodal intraoral Hodgkin lymphoma is not common. We report the case of a 78-year-old male patient with ulcer of the mandibular oral mucosa that was not cured for about 3 weeks. In biopsy and histopathologic examination, it was found to be extranodal intraoral Hodgkin lymphoma. Early diagnosis of oral lesions led to early detection of lesions of the opposite neck lymph node in an additional PET-CT scan We report this case and review relevant literature KCI Citation Count: 0